126 Analysis of genotype phenotype correlation in multiple sclerosis. Issue 3 (9th February 2012) - Baker, K; Cossburn, M D; Ingram, G; Hirst, C L; Loveless, S; Pickersgill, T P; Robertson, N P
Abstract : There is increasing evidence for genetic contribution to aetiology of multiple sclerosis (MS) and disease phenotype. The prolonged clinical course in MS limits collection of longitudinal phenotypic data. Alternative approaches include MS Severity Scale (MSSS), or extremes of outcome (EOO) comparisons. We have studied phenotypic impact of 14 non-HLA disease associated single nucleotide polymorphisms (SNPs) in a population with detailed longitudinal clinical data. Genotypes were analysed from 1007 MS patients followed for a mean of 10.4 years. Cox regression was used to test time to disability milestones (EDSS 4, 6, 8) and secondary progression (SP). Association with MSSS was tested using ANCOVA and EOO with χ 2 . TYK2 (rs34536443) was associated with time to EDSS 4 (HR (95% CI) 1.3 (1.03.70), p=0.03) and EDSS 6 (HR 1.5 (1.1.0), p=0.01), and there was a trend towards association with MSSS (p=0.07) and EOO (p=0.08). KIF21B (rs12122721) was associated with time to EDSS 8 (HR 1.4 (1.02.9), p=0.03) and SP (HR 1.3 (1.1.5), p=0.02). CD58 (rs2300747) was associated with MSSS (p=0.03) and EOO (p=0.05), but was not associated with time to EDSS milestones. Non-HLA genotypes are unlikely to have a clinical impact on prediction of prognosis. In addition, use of different methodologies to analyse phenotype may produce conflicting results. There is a need for standard analytical methods to ensure that true phenotypic effects are detected.